The Stem Sap Flow and Water Sources for Tamarix ramosissima in an Artificial Shelterbelt With a Deep Groundwater Table in Northwest China - Liu, Feiyao; You, Quangang; Xue, Xian; Peng, Fei; Huang, Cuihua; Ma, Shaoxiu; Pan, Jing; Shi, Yaofang; Chen, Xiaojie (Frontiers in Plant Science, 2022)
The shelter forest belt between Oasis and the desert plays a vital role in preventing aeolian disaster and desertification in arid regions of northwest China. Tamarix ramosissima (T. ramosissima), a typical perennial and native xerophyte shrub in Northwest China, grows naturally or is widely used in building the artificial shelter forest belt. The balance between water consumption and the availability of water determines the survivorship and growth of T. ramosissima. How the T. ramosissima cope with extremely low rainfall and deep groundwater table remains unknown. The temporal dynamics and correlation between stem sap flow (SSF) of T. ramosissima and the soil moisture from shallow to deep soil layers (400 cm) were investigated, and isotopic partitioning was used to track the water source for T. ramosissima. Results showed that the daily SSF of T. ramosissima was positively correlated with air temperature (Ta), photosynthetically active radiation (PAR), and vapor pressure deficit (VPD). No significant relationship between the daily SSF and soil moisture at shallow (0-40 cm) and middle (40-160 cm) soil layers was observed, while the oxygen isotope partitioning showed that the T. ramosissima uptakes water mainly (>90%) from deep soil water (160-400 cm) and groundwater (910 cm). Diurnally, the SSF of T. ramosissima showed a hysteresis response to the variation of PAR, Ta, and VPD, which suggest that water stress on the transpiration with the increasing of PAR, Ta, and VPD. Our results indicate that PAR, Ta, and VPD are dominant factors that control the SSF of T. ramosissima, not precipitation and shallow soil moisture; the deep soil water and groundwater is the primary source for T. ramosissima in a drastic environment. Moreover, these results provide essential information for proper water resource management during the region vegetation restoration and ecological reafforestation in the water-limited regions.